Análise de ensaio de fator de potência em transformadores de corrente com variação de frequência utilizando o instrumento de testes CPC-100 - NASCIMENTO, Cleiton Marinho (2018)
This work brings an analysis of isolation potency factors tests on high tension current transformers with a variance of frequency spectrum, considering that on high tension systems the electromagnetic influences could impact directly the results. The methodology here shown a propose solution to minimize, or even suppress these electromagnetic influences. This propose consist in a variation of the frequency during the test, avoiding influences on the fundamental frequency 60Hz and its harmonics. It was used the test instrument CPC-100 for this work on the frequency variation test. Measures were taken on two current transformers to demonstrate the efficiency of the procedure. One transformer was in good condition. The other was in bad condition, and out of service.